Promoting and Sustaining Positive Personal Health Behaviors – Putting the Person First. (21st November 2018) - Teyhen, Deydre S; Robbins, Dennis; Ryan, Barbara Agen
Abstract: Amidst the national debate on the future of health care, there must be a focus on how individuals, communities, and the system need to change to promote and sustain health rather than reactively treat sickness and disability. To transition from a health care system to a "System for Health", we need to move from a patient-focused to a person-focused position. A system that focuses on improving personal decisions related to activity, nutrition, sleep, and tobacco-free living could have a profound impact on health and well-being. The delivery of health, instead of just health care, entails more than just preventing sickness and disability; it requires focusing on building personal wellness, resilience, and endurance. Engaging the individual person to embrace a healthier lifestyle through education, incentives, and technology we can have a positive impact on reducing costs and improving health outcomes. The purpose of this commentary is three-fold: (1) to address the need to implement prescriptions for health, (2) advocate for the need for a person-centric model to help our health care system transition to a system for health, and (3) demonstrate how simple behavior changes can help drive the change to health.